Why to get a 2nd diploma? Is it life-long learning or the outcome of state intervention in educational choices? - Júlia Varga (Hungarian Academy of Sciences, Institute of Economics, 2006)
This paper analyzes the determinants and labour market effects of further higher education studies of graduates, the factors that induce them to switch to other fields (switching decision) and in comparison the determinants of deciding upon deepening their knowledge (to proceed with further higher educational studies in the original field of study) and its labour market consequences. Based on data from a follow-up survey of Hungarian Higher Education Graduates the paper demonstrates that graduates who obtained their first diploma in other than their most preferred field specialisation are more likely to participate in further higher education studies and to switch to another field. In addition, this paper finds some evidence that those, who switch fields, lose a part of their human capital in the short run. The results suggest that state intervention in the supply of field specialities in higher education or the inelasticity of these supplies may lead to further higher education studies of graduates and to a wastage of resources.
Keywords: I22; J24; J44; J62; 330; demand for schooling; human capital; Akademiker; Studium; Studienfach; Qualifikation; Arbeitsmobilität; Ungarn